METTL3 Is Suppressed by Circular RNA circMETTL3/miR-34c-3p Signaling and Limits the Tumor Growth and Metastasis in Triple Negative Breast Cancer - Ruan, Han-guang; Gu, Wen-chao; Xia, Wen; Gong, Yan; Zhou, Xue-liang; Chen, Wen-yan; Xiong, Juan (Frontiers in Oncology, 2021)
Despite N6-methyladenosine (m6A) is functionally important in various biological processes, its role in the underlying regulatory mechanism in TNBC are lacking. In this study, we investigate the pathological role and the underlying mechanism of the m6A methylated RNA level and its major methyltransferase METTL3 in the TNBC progression. We found that the m6A methylated RNA was dramatically decreased in TNBC tissues and cell lines. Functionally, we demonstrated that METTL3 inhibits the proliferation, migration, and invasion ability of TNBC cells. Moreover, we found METTL3 is repressed by miR-34c-3p in TNBC cells. On the mechanism, we found that circMETTL3 could act as a sponge for miR-34c-3p and inhibits cell proliferation, invasion, tumor growth and metastasis by up-regulating the expression of miR-34c-3p target gene METTL3. In conclusion, our study demonstrates the functional importance and regulatory mechanism of METTL3 in suppressing the tumor growth of TNBC.